A Meta-Analysis of Problem-Based Learning Integrated with Ethnomathematics to Improve Children's Mathematical Literacy in the 21st Century - Imroatus Sholihah, Farid (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
There are many applications of problem-based learning models in education, but there is no comprehensive study of the effect of problem-based learning models integrated with ethnomathematics to improve children's mathematical literacy. This study aims to analyse the problem-based learning model integrated with ethnomathematics on children's mathematical literacy in a meta-analysis. The eligibility criteria for this study are research data obtained from journals published in 2023-2025; research must be indexed by Science Technology Index (SINTA) or Scopus; Research must be relevant and report complete research data to calculate the effect size (ES) value. Data analysis with the help of JASP 0.19.30 and Microsoft Excel applications. The results of this study concluded that the 20 effect sizes analysed explained the effect of the problem-based learning model integrated with ethnomathematics on children's mathematical literacy in 21st century learning with a value of (rRE = 1.42; Z = 9.817; p < 0.001) a very strong effect size category. This finding provides positive benefits for the world of education in the implications of problem-based learning models integrated with ethnomathematics in encouraging mathematical literacy in children.Â